Mechanisms of fibrous cap formation in atherosclerosis - Alonso-Herranz, Laura; Albarrán-Juárez, Julián; Bentzon, Jacob Fog (Frontiers in Cardiovascular Medicine, 2023)
The fibrous cap is formed by smooth muscle cells that accumulate beneath the plaque endothelium. Cap rupture is the main cause of coronary thrombosis, leading to infarction and sudden cardiac death. Therefore, the qualities of the cap are primary determinants of the clinical outcome of coronary and carotid atherosclerosis. In this mini-review, we discuss current knowledge about the formation of the fibrous cap, including cell recruitment, clonal expansion, and central molecular signaling pathways. We also examine the differences between mouse and human fibrous caps and explore the impact of anti-atherosclerotic therapies on the state of the fibrous cap. We propose that the cap should be understood as a neo-media to substitute for the original media that becomes separated from the surface endothelium during atherogenesis and that embryonic pathways involved in the development of the arteria media contribute to cap formation.